Spirituality in sport psychology consulting - Guinto, M. L. M. (Advances in mental skills training, 2021)
The seeming ephemeral and elusive qualities of spirituality have isolated it from the scientific study of sport psychology for many years. Efforts to integrate spirit-uality into sport psychology consultations were initially met with resistance as they appeared to cast doubt on the scientific credibility of an emerging discipline. It was argued that, contrary to the self-regulation and internal control espoused by sport psychology, spiritual practices relinquished control to forces outside the self. Studies that identified self-belief as the most important feature of mental toughness among highperforming athletes further reinforced the need to promote reliance on psychological and physical resources, rather than on external spiritual powers that cannot be measured. However, studies in the psychology and sociology of sport have provided sup-port for the intersection of spirituality and sports. Drawing from earlier studies on the strong influence of beliefs on cognitions, emotions, and behaviors, several scholars claimed that spiritual convictions represent a legitimate area of investigation in sports. Among the points raised in defense of the value of spirituality in sports are its contributions to enhancing sport performance and promoting overall wellbeing, offering meaning in adversity such as defeat or injury, and providing coping mechanisms to deal with stress and anxiety. Moreover, sport psychology professionals argued for the importance of spiritual awareness in sport psychology practice and called for the integration of spirituality in the design and conduct of intervention programs. Thus, instead of keeping spirituality out of sport psychology consulting, including it as a helpful tool in the development of athletes is encouraged where appropriate. The accounts shared by the Filipino elite athletes in this chapter reveal how spirituality infused their sport experience, even before any formal incorporation of their religious beliefs and practices in their training and competition. In a way, this simplifies the work of the sport psychology consultant, who wishes to utilize existing beliefs and practices into the consulting relationship. On the other hand, the consultant must also assess how such beliefs and practices facilitate or hinder sport performance. Although spirituality has been found to provide purpose, perspective, and prayer as reservoirs of meaningful attributions and psychospiritual resources, it can also hinder personal growth and wellbeing when it promotes guilt, shame, and anxiety. For instance, if the athlete believes that defeat is a punishment from God, then this may result in negative views of oneself; blaming of others; or alienation from God, who is now considered punitive. Ultimately, the goal of integrating spirituality into sport participation and performance is to help athletes flourish as individuals.